Research Progress on Polydopamine Nanoparticles for Tissue Engineering - Tang, Yanmei; Tan, Yu; Lin, Kaili; Zhu, Min (Frontiers in Chemistry, 2021)
Tissue engineering is an interdisciplinary field that aims to develop biological substitutes for the replacement, repair, or enhancement of tissue function. The physical and chemical characteristics of biomaterials exert a profound influence on the biological responses and the following biofunction. Nanostructured coatings have been widely applied as an effective surface modification strategy to improve the bioactivity of biomaterials. Especially, polydopamine and polydopamine-derived nanoparticles are found with excessive adhesiveness, redox activity, photothermal conversion capacity, paramagnetism and conductivity other than excellent biocompatibility, and hydrophilicity. In this article, advances about polydopamine nanoparticles in tissue engineering applications are reviewed, including the repair of bone, cartilage, skin, heart, and nerve, to provide strategies for future biomaterial design.